PEMILIHAN FITUR KEPUTUSAN KREDIT BERBASIS MAXIMAL INFORMATION COEFFICIENT (MIC) : SUATU GAGASAN AWAL - Pramesti, Hernawati (Universitas Slamet Riyadi, 2021)
The need for effective risk management means that banks must begin to lookfor continuous improvement in the techniques used for credit analysis byproducing the development and application of various quantitative models. -payments from consumers and the risk of default. This initial idea will be carriedout using an approach that has never been done in studies related to creditscoring, where the method of selecting the independent variable MaximalInformation Coefficient (MIC) to get the best credit decision.